China and the WTO: Progress, Perils, and Prospects - Economy, Elizabeth C.; Chang, Gordon G.; Cohen, Jerome A.; Yu, Peter K. (Columbia Journal of Asian Law, 2003)
In November 2001, member states of the World Trade Organization (“WTO”) approved the proposal to admit China to the international trading body in the Doha Ministerial Conference. After fifteen years of exhaustive negotiations, China formally became the 143rd member of the WTO on December 11, 2001. To reflect on this event and to explore its ramifications, this panel brings together a wide variety of experts. We have optimists and pessimists; inside experts and outside specialists; academics, government officials, and legal practitioners. When commentators analyze the effects of China’s entry into the WTO, they usually fall into one of two camps-the optimists or the pessimists–or a hybrid between the two, which considers China’s entry a “double-edged sword.”